Nahdlatul Ulama and Digital Polarization of Sunni Opinion on the Iran–Israel Conflict - Frans Tory Damara Pradipta Pradipta; Yobi (LAKPESDAM MWCNU Palengaan, 2026)
This study examines the digital polarization of Sunni Muslim opinion regarding the Iran–Israel conflict and the moderating role of Nahdlatul Ulama (NU) in Indonesia. The research focuses on how social media platforms such as YouTube, TikTok, and X (Twitter) contribute to the spread of sectarian narratives and ideological contestation within Indonesian Muslim digital discourse. Using a qualitative descriptive approach and digital discourse analysis, this study analyzes online narratives, institutional statements, and digital content produced by NU-affiliated media platforms. The findings show that digital polarization is intensified by algorithm-driven communication systems that amplify emotional and identity-based content related to Iran, Palestine, and Shia identity. In response, Nahdlatul Ulama promotes moderate digital narratives through the framework of Islam Nusantara, emphasizing humanitarian values, peaceful coexistence, tolerance, and diplomatic approaches. This study concludes that NU plays a significant role in reducing sectarian polarization and strengthening religious moderation within Indonesian digital society. Penelitian ini mengkaji polarisasi digital opini Muslim Sunni terhadap konflik Iran–Israel serta peran moderasi Nahdlatul Ulama (NU) di Indonesia. Penelitian berfokus pada bagaimana media sosial seperti YouTube, TikTok, dan X (Twitter) berkontribusi terhadap penyebaran narasi sektarian dan kontestasi ideologi dalam ruang digital Muslim Indonesia. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan analisis wacana digital terhadap narasi media sosial, pernyataan institusional, dan konten digital yang diproduksi media afiliasi NU. Hasil penelitian menunjukkan bahwa polarisasi digital diperkuat oleh sistem algoritma media sosial yang mendorong penyebaran konten emosional dan berbasis identitas terkait Iran, Palestina, dan identitas Syiah. Sebagai respons, Nahdlatul Ulama membangun narasi digital moderat melalui konsep Islam Nusantara yang menekankan nilai kemanusiaan, toleransi, koeksistensi damai, dan pendekatan diplomatik.